2017
DOI: 10.3389/fmicb.2017.01055
|View full text |Cite
|
Sign up to set email alerts
|

The Fungal Pathogen Candida glabrata Does Not Depend on Surface Ferric Reductases for Iron Acquisition

Abstract: Iron acquisition is a crucial virulence determinant for many bacteria and fungi, including the opportunistic fungal pathogens Candida albicans and C. glabrata. While the diverse strategies used by C. albicans for obtaining iron from the host are well-described, much less is known about the acquisition of this micronutrient from host sources by C. glabrata – a distant relative of C. albicans with closer evolutionary ties to Saccharomyces cerevisiae, which nonetheless causes severe clinical symptoms in humans. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 94 publications
(119 reference statements)
1
35
0
Order By: Relevance
“…Considering that increased expression of ERG11 and ERG4 is one of the common mechanisms of azole resistance in other pathogenic fungi, we concluded that the overexpression of the ERG4 and ERG11 homologs, which may be caused by quadruplication of the genomic region, might be the main cause of ketoconazole resistance in M. pachydermatis KCTC 27587. We note that the genes encoding homologs of ferric reductases, MP87_02943 and MP87_02944, in the quadruplicated region were also more strongly expressed in M. pachydermatis KCTC 27587, which may also influence susceptibility of the yeast to ketoconazole as the enzyme has been shown to contribute to azole resistance [31,32]. Transcript levels of two other genes in the quadruplicated region, encoding a hypothetical protein (MP87_02949) and the homolog of S. cerevisiae Sip1 domain containing protein (MP87_02972), respectively, were also significantly increased by >10-fold.…”
Section: Fig 4 Confirmation Of Gene Copy Numbers In the Quadruplicamentioning
confidence: 85%
“…Considering that increased expression of ERG11 and ERG4 is one of the common mechanisms of azole resistance in other pathogenic fungi, we concluded that the overexpression of the ERG4 and ERG11 homologs, which may be caused by quadruplication of the genomic region, might be the main cause of ketoconazole resistance in M. pachydermatis KCTC 27587. We note that the genes encoding homologs of ferric reductases, MP87_02943 and MP87_02944, in the quadruplicated region were also more strongly expressed in M. pachydermatis KCTC 27587, which may also influence susceptibility of the yeast to ketoconazole as the enzyme has been shown to contribute to azole resistance [31,32]. Transcript levels of two other genes in the quadruplicated region, encoding a hypothetical protein (MP87_02949) and the homolog of S. cerevisiae Sip1 domain containing protein (MP87_02972), respectively, were also significantly increased by >10-fold.…”
Section: Fig 4 Confirmation Of Gene Copy Numbers In the Quadruplicamentioning
confidence: 85%
“… 2013 ) and C. glabrata (Srivastava, Suneetha and Kaur 2014 ), which heavily rely on the reductive pathway for iron uptake to facilitate growth and virulence (Srivastava, Suneetha and Kaur 2014 ; Gerwien et al . 2016 , 2017 ). In contrast, while A. fumigatus siderophore synthesis mutants were dramatically attenuated in virulence (Hissen et al .…”
Section: Ironmentioning
confidence: 99%
“…However, our own work has shown that both Fre6 and Fre8 might have roles other than ferric or cupric reduction in C. glabrata , since this fungus does not exhibit evident surface ferric reductase activity (Gerwien et al . 2017 ). Finally, low-affinity broad-spectrum metal transporters for iron, copper and zinc have been identified in S. cerevisiae (Fet4) (Dix et al .…”
Section: Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several important differences in iron homeostasis control have also been observed between C. glabrata and other model yeast species. For instance, the deletion of the C. glabrata ferric reductase encoding genes FRE8 and FRE6 does not seem to impact the C. glabrata extracellular iron uptake or extracellular ferric reduction activities, in contrast to what has been shown in S. cerevisiae and C. albicans ( Gerwien et al, 2017 ). Still, these two genes are induced by iron starvation ( Nagi et al, 2016 ; Gerwien et al, 2017 ) and regulated by Aft2 (this work) and Aft1 ( Gerwien et al, 2017 ), respectively.…”
Section: Discussionmentioning
confidence: 90%